Evaluating the Effectiveness of Indonesia’s Government Policy in Optimizing the Utilization of ATA Carnet as a Trade Facilitation Instrument - Erwan Bagja Erawan; Rudi Bratamanggala (PT. Publikasiku Academic Solution, 2026)
This study looks at how well the Indonesian government's policy is working to make better use of the ATA Carnet as a tool to help with trade, especially in the bigger picture of aligning with international rules and moving towards more digital customs processes. The ATA Carnet is a temporary permit that makes it easier to move goods across borders. It is based on the Istanbul Convention from 1990 and is managed by the International Chamber of Commerce and the World Customs Organization around the world. Even though Indonesia officially joined the ATA Carnet system together with the Indonesian Chamber of Commerce and Industry (KADIN) and the Directorate General of Customs and Excise (DJBC), the number of people using it is still much lower compared to countries like Singapore and South Korea in the same region. The study used a framework that mixes legal analysis with policy evaluation, looking at both the rules and how well the regulations work in practice, along with how well the institutions are performing. Information comes from official documents by ICC and WCO from 2023 to 2025, OECD trade facilitation reports, national customs reports, and insights gathered from different people involved. The results show that Indonesia's ATA Carnet policy works to some extent, but it is not very effective. This is because there are too many overlapping rules, not enough people know about the policy, and different government agencies aren't working together well enough.